Induced nitric oxide synthetase and peroxiredoxin expression in intramucosal poorly differentiated gastric cancer of young patients. (April 2014) - Hirahashi, Minako; Koga, Yutaka; Kumagai, Reiko; Aishima, Shinichi; Taguchi, Kenichi; Oda, Yoshinao
<x xml:space="preserve">Abstract</x> To investigate the relationship between oxidative stress and gastric carcinogenesis of poorly differentiated adenocarcinoma in young patients, we analyzed the surgically resected specimens of 22 young patients (21–30 years) and 29 older patients (41–72 years) with intramucosal gastric cancer of the poorly differentiated type. We used immunohistochemical staining to evaluate the expression of 8‐hydroxydeoxyguanosine (8OHdG), induced nitric oxide synthetase (iNOS), and antioxidant enzymes (thioredoxin [TRX] and peroxiredoxin [PRDX1, 2 and 3]). We assessed these proteins in the cancer, noncancerous gastric foveolar epithelium and noncancerous mucosal neck. In both the young and older patient groups, the 8OHdG and TRX expressions were gradually increased in cancer cells compared with the noncancerous foveolar epithelial cells and the noncancerous mucosal neck cells (P < 0.001). Although the iNOS and PRDXs expressions were increased in the noncancerous mucosal neck cells compared with the noncancerous foveolar epithelial cells, regardless of age (P < 0.001), the iNOS and PRDX2 expression in the cancer cells were significantly reduced in the young patients compared with the older patients (P < 0.001, P < 0.05). In conclusion, the reduced expression of iNOS or PRDX2 may play an important role in the carcinogenesis of gastric cancer associated with Helicobacter pylori‐induced chronic active gastritis in young patients.